2019
DOI: 10.15282/ijame.16.2.2019.18.0505
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Experimental Investigation of using an Extractor in the Vertical Gravitational Flash Tank Separator

Abstract: The vertical gravitational flash tank separator can be used to increase the performance of a refrigeration cycle. Using the vertical gravitational flash tank separator improves the effective area and enhances the heat transfer coefficient inside the evaporator. However, the vertical gravitational flash tank separator still needs further investigation to improve its performance. This paper provides an investigation study to demonstrate the improvement of separation efficiency using an extractor inside the verti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The no slip wall was applied for the wall boundary. Six cases were simulated for the same domain of the horizontal tube, each case corresponding to a particular mass flow rate that was used in the experiments [31]. Table 3…”
Section: Figure 4 Computational Domain Of the Horizontal Tube Geometrymentioning
confidence: 99%
“…The no slip wall was applied for the wall boundary. Six cases were simulated for the same domain of the horizontal tube, each case corresponding to a particular mass flow rate that was used in the experiments [31]. Table 3…”
Section: Figure 4 Computational Domain Of the Horizontal Tube Geometrymentioning
confidence: 99%
“…The coefficient of performance (COP) and energy consumption need more attention to provide high performance with low energy consumption of a vapour compression refrigeration system. The vapour injection technique using vertical gravitational flash tank separator was used to improve the COP [11,15,[35][36][37]. Winandy and Lebrun [38] reported that the vapour injection contributes to raise the compressor capacity with constant COP.…”
Section: Vapour Compression Cyclementioning
confidence: 99%
“…The vapour compression refrigeration system consists of four main components named: compressor, condenser, expansion device, and evaporator [2][3][4][5][6][7][8]. These components are connected in order to produce the refrigeration effect through thermodynamic processes: compression, condensation, expansion, and evaporation [9][10][11][12][13][14]. There are man thermodynamic losses associated with isentropic vapour compression and constant enthalpy expansion due to high discharge temperature of the refrigerant, large power consumptions, rise in the condenser heat rejection, large throttling losses and drop in refrigeration capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Two-phase flow patterns represent the behavior of the two-phase flow and can be found in many forms which depend on the operating conditions. The two-phase flow pattern influences the performance of some industry devices such as vertical flash tank separators for the liquid separation [5], [6].…”
Section: Introductionmentioning
confidence: 99%